Criação de valor em pequenas empresas de automação industrial do Vale do Sinos pela interação entre capitais humano, relacional e estrutural - Fogaça, Pablo (Universidade do Vale do Rio dos Sinos, 2017)
Small enterprises employ automation in order to improve their competitiveness, which is traduced in increasing reliability, efficiency, and costs reduction. They also reduce costs related to legal aspects associated with safety, health, environment, and innovation, as well. In several processes, machines relplace persons; nevertheless, automated systems depend on human beings to be created and improved. Value creation is intrinsically linked to knowledge and its use. This qualitative and exploratory research relates to a multiple case studies in which we intended to understand and explain how Small Automation Enterprises (SAE) placed at Vale do Sinos, articulate their Intellectual Capital (IC) to value creation both internally and jointly with their Big Customers Enterprises (BCE). To achieve such goal, there were reviewed the concepts of IC and its classification – Human, Relational, and Structural Capitals (HC, RC, SC). From the theoretical review, there were created categories for analysis for each type of capital, and applied semistructured questionnaries to managers of four SAEs and of six BCEs that keep business each other. Also, N-Vivo software was employed to perform analysis content of the interviews. As results, there can be highlighted: (i) SAEs do not have concern related to their knowledge management, because their knowledge retention is within their managers; (ii) such firms has few or almost none knowledge about IC, which is corroborated by academic studies; (iii) such firms give high weigth to familiar values of their collaborators and their relationships as a HC attribute, what brings evidences that they understand HC as RC, and it confirms that there is overlapping of understanding between different intellectual capital categories, as regarded by authors as Dumay (2009; 2013); (iv) RC identified in the SAEs chain consists in their internal relations, as well as in the relationships between such firms and their suppliers and customers; (v) SAEs consider that their suppliers add value through three key factors: quality, fair price, and terms attainment. It is corroborated by academic literature, as well. This research identified, as unanimity, the problem of term accomplishment as the main source of conflict in the relationship between SAEs and BCEs.
Keywords: Pequenas empresas de automação; Capital humano; Capital relacional; Capital estrutural; Criação de valor; Small automation firms; Human capital; Relational capital; Relational capital; Structural capital; Value creation; ACCNPQ::Engenharias::Engenharia de Produção